Structural cells are key regulators of organ-specific immune response - Krausgruber, Thomas (Nature, 2020)
The mammalian immune system implements a remarkably effective set of mechanisms for fighting pathogens(1). Its main components are hematopoietic immune cells, including myeloid cells that control innate immunity and lymphoid cells that constitute adaptive immunity(2). However, immune functions are not unique to hematopoietic cells, and many other cell types display basic mechanisms of pathogen defence(3–5). To advance our understanding of immunology outside the haematopoietic system, here we systematically investigate the regulation of immune genes in the three major types of structural cells: epithelium, endothelium, and fibroblasts. We characterize these cell types across twelve organs in mice, using cellular phenotyping, transcriptome sequencing, chromatin-accessibility profiling, and epigenome mapping. This comprehensive dataset revealed complex immune gene activity and regulation in structural cells. The observed patterns were highly organ-specific and seem to modulate the extensive interactions between structural cells and haematopoietic immune cells. Moreover, we identified an epigenetically encoded immune potential in structural cells under tissue homeostasis, which was triggered in response to systemic viral infection. This study highlights the prevalence and organ-specific complexity of immune gene activity in non-haematopoietic structural cells, and it provides a high-resolution, multi-omics atlas of the epigenetic and transcriptional networks that regulate structural cells in the mouse.